2018
DOI: 10.1038/s41396-018-0223-9
|View full text |Cite
|
Sign up to set email alerts
|

Single cell genomic and transcriptomic evidence for the use of alternative nitrogen substrates by anammox bacteria

Abstract: Anaerobic ammonium oxidation (anammox) contributes substantially to ocean nitrogen loss, particularly in anoxic marine zones (AMZs). Ammonium is scarce in AMZs, raising the hypothesis that organic nitrogen compounds may be ammonium sources for anammox. Biochemical measurements suggest that the organic compounds urea and cyanate can support anammox in AMZs. However, it is unclear if anammox bacteria degrade these compounds to ammonium themselves, or rely on other organisms for this process. Genes for urea degra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 82 publications
2
37
0
1
Order By: Relevance
“…Recent studies demonstrated the utilization of cyanate as a substrate for ammonia oxidation and nitrogen assimilation by thermophilic and marine AOA and marine anammox organisms (24)(25)(26). In the AOA strain Nitrososphaera gargensis, this capability is based on the release of ammonia from cyanate by the enzymatic activity of cyanate hydratase (cyanase) (24).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies demonstrated the utilization of cyanate as a substrate for ammonia oxidation and nitrogen assimilation by thermophilic and marine AOA and marine anammox organisms (24)(25)(26). In the AOA strain Nitrososphaera gargensis, this capability is based on the release of ammonia from cyanate by the enzymatic activity of cyanate hydratase (cyanase) (24).…”
Section: Resultsmentioning
confidence: 99%
“…Urea and cyanate are two dissolved organic nitrogen compounds ubiquitously present in seawater 26 , and also detected in marine sediment porewater 27 . The utilizations of these two compounds have been suggested for Scalindua lineages found in oxygen minimum zones based on chemical measurements 28,29 and supported by single-cell genome sequencing 30 . Here we expand this observation to marine sediments, by unambiguously identifying a urease and two cyanases in a single sediment Ca.…”
Section: Main Textmentioning
confidence: 94%
“…The ability to use cyanate as a source of reductant (i.e., ammonia) and carbon (i.e., carbon dioxide) may also be an important ecological adaptation of ammonia-oxidizing microorganisms, with implications for soil nitrification. Although only a few genomes of ammonia-oxidizing archaea and complete ammonia-oxidizing (comammox) organisms are known to encode cyanases (5,42,43), another but yet unknown enzyme may be involved in the decomposition of cyanate. Kitzinger et al (7) found that an isolate of a marine ammonia-oxidizing archaeon lacking a cyanase can oxidize cyanate to nitrite.…”
Section: Resultsmentioning
confidence: 99%
“…Cyanate (NCO -) is an organic nitrogen compound that has mainly been of interest in medical science due to its negative effect on protein conformation and enzyme activity (e.g., 1), in chemical industry as industrial feedstock, and in industrial wastewater treatment, where it is produced in large amounts, especially during cyanide removal (e.g., 2,3). However, in recent years, cyanate received more attention in marine biogeochemistry and microbial ecology, with the discovery of the involvement of cyanate in central nitrogen (N) cycling processes, namely in nitrification and anaerobic ammonia oxidation (anammox) (4,5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation